Synthesis of 1,2-Dimetallic Compounds via Direct Insertion of Zinc Powder in the Presence of InCl3: Synthesis of ortho-Bis-functionalized Aromatics - Klatt, Thomas; Blümke, Tobias D.; Ganiek, Maximilian A.; Knochel, Paul (Synthesis, 2014)
A variety of functionalized 1,2-dizinc reagents can be prepared by an indium-catalyzed insertion of zinc powder into aromatic 1,2-dibromides or 1-bromo-2-triflates. These 1,2-dimetallics undergo Cu- or Pd-catalyzed acylations, allylations, or cross couplings.
Keywords: zinc; 1,2-dimetallic; insertion; cross-coupling; indium(III) chloride